2023
DOI: 10.3390/v15010151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of EGCG Extracted from Green Tea against Largemouth Bass Virus Infection

Abstract: (1) Background: Largemouth bass virus (LMBV) is a major viral pathogen in largemouth bass (Micropterus salmoides) aquaculture that often causes high mortality and heavy economic losses, thus developing treatments to combat this pathogen is of great commercial importance. Green tea is a well-known medicinal plant that contains active ingredients with antiviral, antibacterial, and other biological activities. The goals of this study were to explore the effect and mechanism of green tea source compounds on LMBV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Liu et al found that quercetin had a damaging effect on the particles of SGIV, thereby inhibiting the infective ability of SGIV [27]. Cheng et al used EGCG to treat the LMBV virus and found a significant decrease in the infectivity of LMBV [48]. In the present study, we likewise evaluated the effect of edaravone on SGIV particles.…”
Section: Discussionmentioning
confidence: 68%
“…Liu et al found that quercetin had a damaging effect on the particles of SGIV, thereby inhibiting the infective ability of SGIV [27]. Cheng et al used EGCG to treat the LMBV virus and found a significant decrease in the infectivity of LMBV [48]. In the present study, we likewise evaluated the effect of edaravone on SGIV particles.…”
Section: Discussionmentioning
confidence: 68%
“…While several vaccines and herbal extracts have shown efficacy in preventing LMBV infection, there are currently no approved vaccines or drugs available for its prevention or treatment (Yao et al, 2022;Cheng et al, 2023;Wang et al, 2023;Zhang, M. et al, 2023). Moreover, infected fish with LMBV experience rapid mortality once symptoms appear…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is considered an ideal approach for preventing LMBV infection. Although some candidate vaccines and herbal extracts have been proven to be potent for defending against LMBV infection under laboratory conditions, there is no licensed vaccine or antiviral drug available for preventing or treating LMBV infection (Jia et al, 2022;Yao et al, 2022;Cheng et al, 2023;Wang et al, 2023;Zhang, M. et al, 2023). Therefore, rapid detection and early diagnosis of LMBV remain crucial strategies to prevent the disease's spread and mitigate economic loss.…”
Section: Introductionmentioning
confidence: 99%